Competition between CTL narrows the immune response induced by prime-boost vaccination protocols. - Palmowski, M; Choi, E; Hermans, I; Gilbert, S; Chen, J; Gileadi, U; Salio, M; Van Pel, A; Man, S; Bonin, E; Liljestrom, P; Dunbar, P; et al. (2002)
Recombinant vaccines encoding strings of virus- or tumor-derived peptides and/or proteins are currently being designed for use against both cancer and infectious diseases. These vaccines aim to induce cytotoxic immune responses against several Ags simultaneously. We developed a novel tetramer-based technique, based on chimeric HLA A2/H-2K(b) H chains, to directly monitor the CTL response to such vaccines in HLA-A2 transgenic mice. We found that priming and boosting with the same polyepitope construct induced immune responses that were dominated by CTL of a single specificity. When a mixture of viruses encoding single proteins was used to boost the polyepitope primed response, CTL of multiple specificities were simultaneously expanded to highly effective levels in vivo. In addition, we show that a preexisting response to one of the epitopes encoded within a polyepitope construct significantly impaired the ability of the vaccine to expand CTL of other specificities. Our findings define a novel vaccination strategy optimized for the induction of an effective polyvalent cytotoxic response.